Noxious weed monitoring (year 14) & mapping at the U.S. Air Force Academy and Farish - Smith, Pam, author; Greenwell, Amy, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2019)
This report summarizes the results of the past fourteen years of population monitoring of noxious weeds at the U.S. Air Force Academy ("the Academy") and Farish Recreation Area ("Farish"). Basewide monitoring has been conducted at the Academy at five year intervals: 2002, 2007, 2012 and 2018. (2002, 2007, 2012 and 2017 at Farish). In between years, areal mapping at known sites was conducted at the Academy for species with low cover and permanent plots were used to monitor widespread noxious weed species at the Academy (2018) and Farish (2016). These data are used to determine population trends. The 2018 basewide survey included 26 species that were mapped across the Academy and Farish. Four new species of noxious weeds were included in the 2018 survey, three new noxious weeds at the Academy and one at Farish. Site plans are provided as separate attachments to assist with weed management activities in 2019 for three areas: Northeast Jack's Valley Seep, Farish Fen with a globally imperiled (G2) grass species Porter's feathergrass (Ptilogrostis porteri) and the Farish site with the newly discovered (2018) orange hawkweed.
Prepared for: U.S. Air Force Academy Department of Natural Resources.
May 2019.
Keywords: Colorado; noxious weeds; weed control; vegetation surveys